Ten years of marine evolutionary biology—Challenges and achievements of a multidisciplinary research initiative. (7th January 2023) - Johannesson, Kerstin; Leder, Erica H.; André, Carl; Dupont, Sam; Eriksson, Susanne P.; Harding, Karin; Havenhand, Jonathan N.; Jahnke, Marlene; Jonsson, Per R.; Kvarnemo, Charlotta; Pavia, Henrik; Rafajlović, Marina; et al.
Abstract: The Centre for Marine Evolutionary Biology (CeMEB) at the University of Gothenburg, Sweden, was established in 2008 through a 10‐year research grant of 8.7 m€ to a team of senior researchers. Today, CeMEB members have contributed >500 scientific publications, 30 PhD theses and have organised 75 meetings and courses, including 18 three‐day meetings and four conferences. What are the footprints of CeMEB, and how will the centre continue to play a national and international role as an important node of marine evolutionary research? In this perspective article, we first look back over the 10 years of CeMEB activities and briefly survey some of the many achievements of CeMEB. We furthermore compare the initial goals, as formulated in the grant application, with what has been achieved, and discuss challenges and milestones along the way. Finally, we bring forward some general lessons that can be learnt from a research funding of this type, and we also look ahead, discussing how CeMEB's achievements and lessons can be used as a springboard to the future of marine evolutionary biology.